Resistance exercise reduces liver fat and its mediators in non-alcoholic fatty liver disease independent of weight loss. Issue 9 (27th June 2011) - Hallsworth, Kate; Fattakhova, Gulnar; Hollingsworth, Kieren G; Thoma, Christian; Moore, Sarah; Taylor, Roy; Day, Christopher P; Trenell, Michael I
Abstract : Background: Lifestyle interventions focusing on weight loss remain the cornerstone of non-alcoholic fatty liver disease (NAFLD) management. Despite this, the weight losses achieved in research trials are not easily replicated in the clinic and there is an urgent need for therapies independent of weight loss. Aerobic exercise is not well sustained and the effectiveness of the better tolerated resistance exercise upon liver lipid and mediators of liver lipid has not been assessed. Methods: Sedentary adults with clinically defined NAFLD were assigned to 8 weeks of resistance exercise (n=11) or continued normal treatment (n=8). Results: 8 weeks of resistance exercise elicited a 13% relative reduction in liver lipid (14.0±9.1 vs 12.2±9.0; p<0.05). Lipid oxidation (submaximal RQ ∆ −0.020±0.010 vs −0.004±0.003; p<0.05), glucose control (−12% vs +12% change AUC; p<0.01) and homeostasis model assessment insulin resistance (5.9±5.9 to 4.6±4.6 vs 4.7±2.1 to 5.1±2.5; p<0.05) were all improved. Resistance exercise had no effect on body weight, visceral adipose tissue volume, or whole body fat mass (p>0.05). Conclusion: This is the first study to demonstrate that resistance exercise specifically improves NAFLD independent of any change in body weight. These data demonstrate that resistance exercise may provide benefit for the management for non-alcoholic fatty liver, and the long-term impact of this now requires evaluation.